Pengembangan Media Pembelajaran Berbasis Android Dengan Pemanfaatan Ispring Suite Pada Mata Pelajaran Akidah Akhlak - Himmah, Faiqotul; Sulaikho, Siti (JoEMS (Journal of Education and Management Studies), 2022)
The purpose of this research is to create an Android-based learning medium using the iSpring Suite, as well as to assess the positive and significant association between the usage of an Android-based Microsoft PowerPoint iSpring Suite as a learning medium. The Research and Development (R&D)approach is used in this investigation. Students from MTsN 3 Jombang participated in the development study trial. The results of the questionnaire on the needs of class VIII students indicate that they have difficulty learning materials that are only sourced from books/LKS and that they require interesting learning media that can be accessed at any time to assist students in learning and as motivation for enthusiasm for learning. The validation results from material experts are 94.20% in the Very Eligible category. The validation results from linguists were 93.75% in the Very Eligible category. The validation results from media experts are 75% in the Eligible category. The average result obtained from the student response questionnaire is 81.02% in the Very Eligible category. The average result of pre-test data is 74.20 and the average result of post-test data is 87.62. The results of the analysis through the t-test with two samples, namely: tcount is greater than ttable, meaning Ha is accepted and Ho is rejected.So, there is a positive and significant effect before using android-based learning media and after using android-based learning media.